2019
DOI: 10.1177/1460458219867231
|View full text |Cite
|
Sign up to set email alerts
|

Detecting associations between dietary supplement intake and sentiments within mental disorder tweets

Abstract: Many patients with mental disorders take dietary supplement, but their use patterns remain unclear. In this study, we developed a method to detect signals of associations between dietary supplement intake and mental disorder in Twitter data. We developed an annotated dataset and trained a convolutional neural network classifier that can identify language use pattern of dietary supplement intake with an F1-score of 0.899, a precision of 0.900, and a recall of 0.900. Using the classifier, we discovered that mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Interestingly, consuming micronutrients post-disaster including earthquakes, floods and massacres showed that micronutrient supplements reduced the risk of PTSD from 75 to 15% [ 53 ]. However, one study using Twitter Sentiment Analysis concluded an individuals with mental health disorders and taking a supplement showed more negative emotions in their tweets [ 54 ]. Unfortunately, this study did not measure the level of micronutrients consumed by the respondents; thus, the cause and effect between hypervigilance and consuming dietary supplements could not be concluded.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, consuming micronutrients post-disaster including earthquakes, floods and massacres showed that micronutrient supplements reduced the risk of PTSD from 75 to 15% [ 53 ]. However, one study using Twitter Sentiment Analysis concluded an individuals with mental health disorders and taking a supplement showed more negative emotions in their tweets [ 54 ]. Unfortunately, this study did not measure the level of micronutrients consumed by the respondents; thus, the cause and effect between hypervigilance and consuming dietary supplements could not be concluded.…”
Section: Discussionmentioning
confidence: 99%
“…The two most notable linguistic dimensions related to sentiment are “positive emotion” and “negative emotion”, both of which have been used in several studies to measure positive and negative emotion in the online users’ posts [ 40 , 41 ]. In this paper, sentiment polarity included three types: positive, neutral, and negative.…”
Section: Methodsmentioning
confidence: 99%
“…We selected only English tweets to develop the concept extraction and relation extraction models. A total of 247,807 tweets that satisfy the criteria were found from a Twitter database we constructed in prior work [34,35] using the Twitter streaming application programming interface (API), covering daily publictweets from 2012 to 2018.…”
Section: Data Collectionmentioning
confidence: 99%